Navigating Trauma Patients and Families Through Unfamiliar Territory. Issue 1 (January 2023) - Lee, Donna B.
Abstract : Background: Trauma teams work diligently to manage the complex medical needs of trauma patients. In addition to medical care, there is also a need to assist patients and their families as they navigate the emotional and physical journey of trauma. The role of trauma nurse navigator was developed to address these holistic needs. Objective: This article aims to describe the implementation of a trauma nurse navigator role. Methods: This article describes the development and implementation of a trauma nurse navigator role at a Level II trauma center in 2018. The trauma nurse navigator serves as a patient resource and utilizes creative problem solving to optimize care. The trauma nurse navigator also serves on the multidisciplinary team, working with providers, nursing staff, rehabilitation staff, and case management to provide seamless care to trauma patients. Results: Implementation of the trauma nurse navigator role was well received by patients, families, and the multidisciplinary trauma team. The trauma nurse navigator role expanded the psychosocial support of trauma patients and increased patient satisfaction. Conclusion: Although other specialties have seen the benefits of including a patient navigator on the team, this is a potential for trauma centers as they strive to provide high-quality patient care.